Legal Implications of Pledge Injuries in Banking Credit Agreements - Anam, Khoirul (Leges Privatae, 2025)
This study examines the legal implications of default (breach of contract) in banking credit agreements in Indonesia. Credit agreements play a crucial role in the banking sector, providing financial support for individuals and businesses. However, defaults in credit agreements have become a significant issue, affecting not only debtors and creditors but also the stability of the financial system. This research employs a normative legal method with a statutory approach, analyzing relevant laws and regulations such as the Indonesian Civil Code (KUH Perdata), Law No. 10 of 1998 on Banking, and OJK Regulations. The findings reveal that default in credit agreements is caused by various factors, including financial incapacity, unfavorable economic conditions, force majeure, bad faith of debtors, and bank mismanagement. The study also highlights the legal consequences of default, which include penalties, asset seizures, and litigation or non-litigation dispute resolution mechanisms. While litigation provides stronger legal certainty, it is time-consuming and costly, whereas non-litigation methods such as mediation and arbitration offer faster and more flexible resolutions. This study emphasizes the need for improved regulatory enforcement and preventive measures, such as enhanced risk assessment, debtor monitoring, and early warning systems to mitigate default risks. Strengthening collaboration between banks, regulators, and the judiciary is also essential to ensure effective legal protection for all parties involved in credit agreements.